A new genus and new species of Aeptini (Hemiptera: Heteroptera: Pentatomidae: Pentatominae) from Australia - Faundez, Eduardo; Rider, David A. (My University, 2019)
The aeptine Mariomella singularis gen. et sp. nov. is described and illustrated from Western Australia. With this new addition, the Aeptini diversity increases to 21 species in nine genera.
Keywords: pentatominae; new taxa; systematics; western australia